2018
DOI: 10.1111/maec.12490
|View full text |Cite
|
Sign up to set email alerts
|

A microbial perspective on the life‐history evolution of marine invertebrate larvae: If, where and when to feed

Abstract: The feeding environment for planktotrophic larvae has a major impact on development and progression towards competency for metamorphosis. High phytoplankton environments that promote growth and development also correlate with a greater abundance of environmental microbes and incidence of pathogenic microbes, making these habitats potentially risky for larvae. Trade‐offs between metabolic processes for growth and immune functionality have been described throughout the animal kingdom and may influence the life‐h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 86 publications
(121 reference statements)
1
16
0
Order By: Relevance
“…However, feeding-associated plasticity typically manifests as reduced gut size and increased arm length relative to body length under low food conditions, and our low bacterial load (P/S) animals were larger in all measurements (body length, gut area, post-oral arm length, anterolateral arm length) besides the body rod, which is not typically plastic in response to food (83). One explanation is that bacterial exposure mediates a trade-off between growth and immune competence during development, as predicted in Carrier et al (82). In this model, larvae expend energy to establish and maintain a molecular and/or cellular immune state that would otherwise be diverted to growth and development in the absence of bacteria.…”
Section: Bacterial Exposure-associated Morphological Plasticitysupporting
confidence: 69%
See 1 more Smart Citation
“…However, feeding-associated plasticity typically manifests as reduced gut size and increased arm length relative to body length under low food conditions, and our low bacterial load (P/S) animals were larger in all measurements (body length, gut area, post-oral arm length, anterolateral arm length) besides the body rod, which is not typically plastic in response to food (83). One explanation is that bacterial exposure mediates a trade-off between growth and immune competence during development, as predicted in Carrier et al (82). In this model, larvae expend energy to establish and maintain a molecular and/or cellular immune state that would otherwise be diverted to growth and development in the absence of bacteria.…”
Section: Bacterial Exposure-associated Morphological Plasticitysupporting
confidence: 69%
“…In this study, we found that the sizes of multiple larval structures were associated with differences in bacterial exposure during development. At first glance, this effect appeared similar to feeding-associated phenotypic plasticity, as planktotrophic larvae consume bacteria, and gut bacteria are associated with digestive and metabolic functions in countless taxa (2,3,7,8), including larval (38,82) and adult sea urchins (27,69). However, feeding-associated plasticity typically manifests as reduced gut size and increased arm length relative to body length under low food conditions, and our low bacterial load (P/S) animals were larger in all measurements (body length, gut area, post-oral arm length, anterolateral arm length) besides the body rod, which is not typically plastic in response to food (83).…”
Section: Bacterial Exposure-associated Morphological Plasticitymentioning
confidence: 83%
“…It has since been observed that additional planktotrophic echinoderms exhibit bacterivory and that this feeding mode is hypothesized to be important, but not essential, to the metabolic requirements of the larva (Pearse et al, 1991;Douillet, 1993;Ayukai, 1994;Moal et al, 1996;Gosselin and Qian, 1997). Based on maximum clearance rates and particle abundance, it is estimated that echinoderm larvae interact with ∼20 million bacteria each day by feeding alone (Carrier et al, 2018a). It is, however, unknown which bacterial (or other microbial) groups that echinoderm larvae may target and whether these microbes are selected strictly for bacterivory or as a symbiont that may be acquired by horizontal transmission.…”
Section: Echinoderms and Their Larvaementioning
confidence: 99%
“…Less of this work, however, has focused on embryonic and larval echinoderms. Echinoderm larvae potentially interact with ∼20 million bacteria each day by feeding alone (Carrier et al, 2018a), and a portion of these bacteria may be consumed through bacterivory, be symbionts acquired by horizontal transmission, or pathogenic bacteria that require an immune response.…”
Section: Pathogenic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation